Controlled transport on the surface of a topological insulator by biased transverse electric field. (28th August 2015) - Da, Haixia
Abstract: We report on the biased transverse electric field sensitive transport of Dirac fermions on the surface of a three-dimensional topological insulator modulated by magnetic superlattices. By using a scattering matrix method, we find that the transmission spectrum for both parallel and antiparallel configurations exhibits asymmetrical features. In addition, the analysis of conductances in different magnetic configurations allows us to obtain controlled magnetoresistence depending on the amplitude of the external electric field. These might make topological insulators good candidates for future spintronics.